Trust, Health Care Relationships, and Chronic Illness - Carole A. Robinson (SAGE Publishing, 2016)
Trust in health care relationships is a key ingredient of effective, high-quality care. Although the indirect influence of trust on health outcomes has long been recognized, recent research has shown that trust has a direct effect on outcomes of care. Trust is important. However, the research on trust is disparate, organized around differing definitions, and primarily focused on patients' trust in physicians. Morse's method of theoretical coalescence was used to further develop and elaborate a grounded theory of the evolution of trust in health care relationships, in the context of chronic illness. This middle-range theory offers a clear conceptual framework for organizing and relating disparate studies, explaining the findings of different studies at a higher conceptual level, and identifying gaps in research and understanding. In addition, the grounded theory is relevant to practice.